The relationship between sleep quality and gait in people with multiple sclerosis: A pilot study - Wlla Abedalaziz; Alham Al-Sharman; Aseel Aburub; Mariem Syrine Latrous; Patrick Esser; Helen Dawes; Khalid El-Salem; Hanan Khalil (World Scientific Publishing, 2024)
Background: Gait deficits are common among people with multiple sclerosis (PwMS). Therefore, investigating factors that may influence walking in PwMS is important. Previous studies in older adults and other neurological populations demonstrated the relationship between sleep quality and gait performance. Despite the fact that the prevalence of poor sleep quality is very high among PwMS, little is known about the effect of sleep quality on gait among PwMS. Objective: This study aimed to explore the relationship between sleep quality and gait performance in PwMS. Methods: Forty-one PwMS participated in the study between February 2019 and December 2019. Participants were asked to walk at a self-selected speed over 10[Formula: see text]m with an inertial measurement unit (IMU) attached over the back. Walking speed, step length (left and right), and step time were calculated. Sleep was estimated objectively using a wrist-worn triaxle-accelerometer; the derived parameters were sleep efficiency (SE) and the number of awakening after sleep onset (NASO). Results: SE significantly correlated with step length ([Formula: see text]). Furthermore, the NASO significantly correlated with gait speed ([Formula: see text]), and step-time ([Formula: see text]). These correlations remained significant even after adjusting for age and disease duration. Conclusion: We observed that when corrected for disease duration and age there were relationships between NASO and SE to gait parameters; these observations warrant further investigations.